2022
DOI: 10.1108/bjm-09-2021-0360
|View full text |Cite
|
Sign up to set email alerts
|

Founder domination, industry environment, and family firms' earnings management

Abstract: PurposeBased on socioemotional wealth theory, the authors explore the impact of founder domination (with the founder as the chairman or CEO) on the earnings management activities of family firms and examine the moderating effect of the industry environment on the above relationship.Design/methodology/approachBased on the multivariate regression model, the authors test the theoretical view on the empirical data of Chinese family-owned listed companies.FindingsThe authors propose and find that under founder domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(225 reference statements)
0
5
0
Order By: Relevance
“…On the contrary, Zhong et al (2022) argued, through the Socio-emotional Wealth theory, that the dominance of family founders in FFs may prevent such firms from engaging in EM activities, due to family influence. This theory holds promise as an explanation for the behavior of family businesses in future research, addressing the emotional needs of the family distinct from financial aspects.…”
Section: Review Of Earnings Management Practicesmentioning
confidence: 99%
“…On the contrary, Zhong et al (2022) argued, through the Socio-emotional Wealth theory, that the dominance of family founders in FFs may prevent such firms from engaging in EM activities, due to family influence. This theory holds promise as an explanation for the behavior of family businesses in future research, addressing the emotional needs of the family distinct from financial aspects.…”
Section: Review Of Earnings Management Practicesmentioning
confidence: 99%
“…Employee participation in the decision-making process creates a good working environment, enhances job satisfaction, increases commitment, and improves productivity (Dede, 2019). Several studies found a significant positive relationship between employee participation and motivation (Wagner III, 1994) And productivity is considered a performance measurement indicator of employees from two dimensions: effectiveness and efficiency (Zhong, Ren, & Wu, 2022). Participative activities within the organization have also been found to have a positive relationship with employee productivity (Rosenberg & Rosenstein, 1980).…”
Section: Relationship Between Productivity and Workers' Participation...mentioning
confidence: 99%
“…H1b: There is a statistically significant relationship between earnings management practices (measured by discretionary accruals) and legal form/ownership structure. Zhong et al (2022) found that industry growth may enhance earnings management, while industrial competition weakens it. Baatwah et al (2021) also reported that specific industry expertise can result in earnings manipulation reduction.…”
Section: )mentioning
confidence: 99%
“…2146-58) supported the beneficial impact of the sector of operation on earnings management. Zhong et al (2022) measured the impact of industrial environment on earnings management activities and revealed that industry growth may increase these activities. Perafan-Pena et al ( 2022) also provided evidence demonstrating the significance of the sector in the relationship to earnings management.…”
Section: )mentioning
confidence: 99%